A Modified Delphi Study for Development of a Pediatric Curriculum for Emergency Medicine Residents. Issue 2 (22nd March 2017) - Mitzman, Jennifer; King, Andrew M.; Fastle, Rebecca K.; Hopson, Laura R.; Hoyle, John D.; Levasseur, Kelly A.; Mitchell, Michael S.; O'Neill, James C.; Pazderka, Philip A.; Perry, Marcia A.; Reynolds, Maegan; Shah, Payal G.; et al.
Abstract: Objectives: Emergency medicine (EM) trainees are expected to learn to provide acute care for patients of all ages. The American Council for Graduate Medical Education provides some guidance on topics related to caring for pediatric patients; however, education about pediatric topics varies across residency programs. The goal of this project was to develop a consensus curriculum for teaching pediatric emergency care. Methods: We recruited 13 physicians from six academic health centers to participate in a three‐round electronic modified Delphi project. Participants were selected on the basis of expertise with both EM resident education and pediatric emergency care. The first modified Delphi survey asked participants to generate the core knowledge, skills, and experiences needed to prepare EM residents to effectively treat children in an acute care setting. The qualitative data from the first round was reformulated into a second‐round questionnaire. During the second round, participants used rating scales to prioritize the curriculum content proposed during the first round. In round 3, participants were asked to make a determination about each curriculum topic using a three‐point scale labeled required, optional, or not needed. Results: The first modified Delphi round yielded 400 knowledge topics, 206 clinical skills, and 44 specific types of experience residents need to prepare for acute pediatric patient care. These were narrowed to 153 topics, 84 skills, and 28 experiences through elimination of redundancy and two rounds of prioritization. The final lists contain topics classified by highly recommended, partially recommended, and not recommended. The partially recommended category is intended to help programs tailor their curriculum to the unique needs of their learners as well as account for variability between 3‐ and 4‐year programs and the amount of time programs allocate to pediatric education. Conclusion: The modified Delphi process yielded the broad outline of a consensus core pediatric emergency care curriculum.